Short rehabilitation training program may improve postural control in children with autism spectrum disorders: preliminary evidences - Caldani, Simona (Sci Rep, 2020)
Autism Spectrum Disorders subjects (ASD) is characterized by postural control deficits. This study aimed to explore the effect of a short postural rehabilitation training program on postural capabilities in children with ASD. Two groups (G1 and G2) of twenty children with ASD of IQ-, sex- and age- matched (mean age 11.7 ± 2.4 years) were included in this study. Posture was recorded by using the Balance Quest from Framiral on unstable platform in three different viewing conditions. The rehabilitation program consisted in two distinct postural control training exercises. Postural recordings were performed twice at T1 and T2 for both groups of children. Between T1 and T2 a 6-minute postural training was performed by the G1 group only, while the G2 group had a 6-minute of rest. Children were allocated randomly to the G1 or G2 groups. At T1, postural instability was similar for both groups of ASD children (G1 and G2) desp+\ite viewing conditions. At T2, we observed an improvement of postural control related to a mixed effect of training rehabilitation but also of test-retest. Knowing the potential of new rehabilitation strategies, the impact of postural control deficit in ASD children needs to be reconsidered. Well design case-control studies are requested to ensure scientific validity of postural rehabilitation training program.